Systematic review: Nurses' safety attitudes and their impact on patient outcomes in acute‐care hospitals - Faisal Khalaf Alanazi; Jenny Sim; Samuel Lapkin (Wiley, 2022)
Abstract Aims The aim of this review was to synthesize the best available evidence on the impact of nurses' safety attitudes on patient outcomes in acute‐care hospitals. Design Systematic review with a narrative synthesis of the available data. Data sources Data sources included MEDLINE, Cumulative Index of Nursing and Allied Health Literature, Scopus and Web of Science Core Collection. Studies published up to March 2021 were included. Review Methods This review was conducted using guidance from the Joanna Briggs Institute for Systematic Reviews and reported as per the Preferred Reporting Items for Systematic Review and Meta‐Analyses guidelines. Results A total of 3,452 studies were identified, and nine studies met the inclusion criteria. Nurses with positive safety attitudes reported fewer patient falls, medication errors, pressure injuries, healthcare‐associated infections, mortality, physical restraints, vascular access device reactions and higher patient satisfaction. Effective teamwork led to a reduction in adverse patient outcomes. Most included studies (N = 6) used variants of the Hospital Survey on Patient Safety Culture to assess nurses' safety attitudes. Patient outcomes data were collected from four sources: coded medical records data, incident management systems, nurse perceptions of adverse events and patient perceptions of safety. Conclusion A positive safety culture in nursing units and across hospitals resulted in fewer reported adverse patient outcomes. Nurse managers can improve nurses' safety attitudes by promoting a non‐punitive response to error reporting and promoting effective teamwork and good communication.